Dimakan Sayang: Turning the Common into the Exclusive, Cassava Bread (Embal) in The Kei Islands, Southeast Maluku, Indonesia - P.M. Laksono (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2021)
This article traces changes in everyday narratives considering cassava bread (embal) in the Kei Islands. Various methods of data collection (participant observation, focused group discussion, and survey) were used, and applied purposively to produce critical narratives on the transformation of local food patterns. These data were collected over a short fieldwork period in 2016 from the villages of Wain, Rumaat, and Langgur in the Kei Islands, Southeast Maluku. As this traditional staple food is being replaced by rice, Kei people are creatively adjusting both their attitudes and appetites towards embal. Both conceptual (noetic)shifts and sensory (taste) shifts are apparent. The typical taste or flavor of embal is increasingly celebrated and regarded as a special blessing. Yet, at the same time, many young Kei are now preferring to eat imported rice more than embal. They are losing their appetite for consuming embal as a daily common food, even as they increasingly adore and celebrate it as a luxurious meal. This suggests that the villagers have become bigger consumers of imported food (rice and noodles) than their city-based counterparts. As such, embal consumers (the local food’s contributors to sovereignty) in the market will continuously be under pressure, diminishing in numbers, in accordance with the rise of its exclusive image. Such is the irony for cassava as food sovereignty in the Kei Islands.